2014
DOI: 10.1002/lary.24631
|View full text |Cite
|
Sign up to set email alerts
|

Gender, race, and electrophysiologic characteristics of the branched recurrent laryngeal nerve

Abstract: African American patients have a higher rate of RLN bifurcation compared to Caucasian patients but no statistically significant difference in distance from NEP. Female patients tend to have longer branching variants of bifid RLNs. RLN motor fibers reside primarily in the anterior branch but may occur in the posterior branch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 17 publications
(57 reference statements)
3
53
0
3
Order By: Relevance
“…The rate of 33% (61 of 185 RLNs) of bifurcated nerves among exposed RLNs in this study is comparable with that of previous reports of 31-43%. [10][11][12][13][14] We also observed that bifurcation occurred adjacent to the ITA and distally to the nerve-artery crossing in 87% of RLNs. Besides the common occurrence of ETB, variable locations of division points along the cervical course of the nerve create many combinations that complicate the dissection and exposure of the nerve.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The rate of 33% (61 of 185 RLNs) of bifurcated nerves among exposed RLNs in this study is comparable with that of previous reports of 31-43%. [10][11][12][13][14] We also observed that bifurcation occurred adjacent to the ITA and distally to the nerve-artery crossing in 87% of RLNs. Besides the common occurrence of ETB, variable locations of division points along the cervical course of the nerve create many combinations that complicate the dissection and exposure of the nerve.…”
Section: Discussionmentioning
confidence: 62%
“…According to our results, the anterior branches of all bifurcated nerves contain motor fibers, in accordance with the findings of previous reports confirming that 100% of anterior branches are pathways of motor activity. 1,10,11,14,16,17 After electrophysiologic stimulation, our results showed that the vast majority of posterior branches were only sensory in function with negative signals recorded on IONM. We recorded motor activity in posterior branches in only 11.5% of the bifid RLNs.…”
Section: Article In Pressmentioning
confidence: 84%
“…They found similar rates between the right and left sides in their subsequent extensive studies and stated that the observations obtained from more extensive series may be more reliable (12). The branching rates were found to be similar between the right and left sides in other studies (9,13,14,18).…”
Section: Discussionmentioning
confidence: 71%
“…The risk of developing nerve paralysis is higher in extralaryngeal branching of the RLN (7,8). The nerve may be vulnerable to compression, traction, and transection due to the diminished caliber of the nerve due to the branching (9). A wide range of branching rates have been reported in studies on branching of the RLN (4).…”
Section: Introductionmentioning
confidence: 99%
“…İONM ça-lışmaları, RLS ön dalının her zaman motor fonksiyona sahip olduğunu, buna karşın %1.14-28.2 oranında arka dalın da motor fonksiyon içerdiği göstermiştir. [61][62][63][64] En yüksek oran (%28.2) Cho ve ark. [63] tarafından bildirilmiş olmakla beraber bu seride dallanma oranı düşüktür (%14.5).…”
Section: Rls'nin Anatomik çEşitliliklerinin Belirlenmesine Katkısıunclassified